2020
DOI: 10.1016/j.colsurfa.2019.124154
|View full text |Cite
|
Sign up to set email alerts
|

Use of N-oxide and cationic surfactants to enhance antioxidant properties of (+)-usnic acid loaded liposomes

Abstract: The influence of the presence of synthetic structurally related N-oxide and corresponding cationic surfactants with different chain lengths on the properties of 1,2-dimyristoyl-sn-glycero-3-phosphocholine liposomes was investigated. Their potentiality as delivery systems of (+)-usnic acid was also evaluated by studying its entrapment efficiency and its antioxidant activity. In fact, (+)-usnic acid has many pharmacological properties that, as many natural substances, are often strictly linked to their antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Pharmaceutics 2020, 12, x 4 of 24 activity, concluding that, more than the charge or the chain length, the combination of both these parameters was fundamental in affecting liposomes physicochemical properties and their ability of influencing the antioxidant effectiveness of usnic acid. Although both studies indicated incorporation of usnic acid into functionalized nanoliposomes to enhance its biological properties, the investigated liposomal suspensions were found to be stable for at least two weeks [19] or less [20], and this issue should be addressed prior to their potential practical usage in the treatment of infections/oxidative stress-related diseases.…”
Section: Of 25mentioning
confidence: 97%
See 4 more Smart Citations
“…Pharmaceutics 2020, 12, x 4 of 24 activity, concluding that, more than the charge or the chain length, the combination of both these parameters was fundamental in affecting liposomes physicochemical properties and their ability of influencing the antioxidant effectiveness of usnic acid. Although both studies indicated incorporation of usnic acid into functionalized nanoliposomes to enhance its biological properties, the investigated liposomal suspensions were found to be stable for at least two weeks [19] or less [20], and this issue should be addressed prior to their potential practical usage in the treatment of infections/oxidative stress-related diseases.…”
Section: Of 25mentioning
confidence: 97%
“…Details of studies concerning usnic acid loaded into nanoliposomes are presented below. Promotion of (+)-usnic acid penetration in biofilm matrix with a consequent increase of antimicrobial activity against S. epidermidis [19] Oxidative stress-related diseases DMPC, Chol and L-prolinol derived surfactants ∼100 from 52 ± 2 to 77 ± 2 Aggregation after two weeks Enhancement of antioxidant properties of (+)-usnic acid [20] Dressing for burn wounds * PC, collagen, PEG/PG 70 n.a. n.a.…”
Section: Product Namementioning
confidence: 99%
See 3 more Smart Citations